Parents Role and the Representation of Bullying Acts in the Drama "The Glory" by Kim Eun Sook and "Pyramid Game" by Choi So I (Semiotics Analysis) - Febrianthy, Cindy; Saragih, Gustaman; Hasbullah, Hasbullah (INFERENCE: Journal of English Language Teaching, 2024)
The phenomenon of bullying is widespread in society and involves a group of people or individuals which is often triggered by pressure from both social norms and class levels in society, making someone a perpetrator or passive observer of bullying behavior. This research is a qualitative study that observes the role of parents in dealing with bullying, and the representation of bullying that occurs in the drama "The Glory" by Kim Eun Sook and "Pyramid Game" by Choi So-i using Roland Barthes' semiotic analysis by explaining the meaning of connotation, denotation and myth. Based on the research results, the role of parents in acts of bullying in the form of negative responses is represented more in the drama "The Glory" by Kim Eun Sook with 71% of views, while the representation of acts of bullying from both dramas shows verbal bullying as much as 44% in the drama "Pyramid Game" by Choi So-I.